Anaplasmosis: An emerging tick-borne disease of importance in Canada. (2018) - Uminski, Kelsey; Kadkhoda, Kamran; Houston, Brett L.; Lopez, Alison; MacKenzie, Lauren J.; Lindsay, Robbin; Walkty, Andrew; Embil, John; Zarychanski, Ryan
Abstract: Human Granulocytic Anaplasmosis (HGA) is an infection caused by the intracellular bacterium Anaplasma phagocytophilum . As a tick-borne disease, the public health impact of HGA continues to increase with range expansion of the disease vector. The clinical presentation of HGA is often a non-specific febrile illness. The presence of leukopenia, thrombocytopenia, and mild hepatic injury are frequently noted on laboratory investigations, which can be important diagnostic clues in attaining an appropriate diagnosis. Herein we present three cases of HGA, highlighting the spectrum of disease by which HGA can manifest. Although each case has their unique features, we outline important shared clinical elements to facilitate an empiric diagnosis while definitive laboratory investigations are pending. Our case series further serves to highlight the critical importance of prompt antimicrobial treatment to reduce morbidity and potential mortality.